2016
DOI: 10.1021/acsami.6b03723
|View full text |Cite
|
Sign up to set email alerts
|

Facile Method to Fabricate Highly Thermally Conductive Graphite/PP Composite with Network Structures

Abstract: Thermally conductive polymer composites have aroused significant academic and industrial interest for several decades. Herein, we report a novel fabrication method of graphite/polypropylene (PP) composites with high thermal conductivity in which graphite flakes construct a continuous thermally conductive network. The thermal conductivity coefficient of the graphite/PP composites is markedly improved to be 5.4 W/mK at a graphite loading of 21.2 vol %. Such a great improvement of the thermal conductivity is ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(79 citation statements)
references
References 40 publications
0
78
1
Order By: Relevance
“…A higher λ value of 1.95 W/ mK was achieved for the graphite/PS composite with 34 vol% colloidal graphite. Feng et al [142] reported one facile method to fabricate highly thermally conductive graphite/PP composites. The obtained λ value of the graphite/PP composite with 21.2 vol% graphite was markedly improved to 5.40 W/mK, mainly ascribed to graphite's orientation and formed thermally conductive networks.…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…A higher λ value of 1.95 W/ mK was achieved for the graphite/PS composite with 34 vol% colloidal graphite. Feng et al [142] reported one facile method to fabricate highly thermally conductive graphite/PP composites. The obtained λ value of the graphite/PP composite with 21.2 vol% graphite was markedly improved to 5.40 W/mK, mainly ascribed to graphite's orientation and formed thermally conductive networks.…”
Section: Carbon-based Fillersmentioning
confidence: 99%
“…[50,51] As shown in Figure 3a,b, the XRD diffraction patterns obtained from Sample A and Sample B are totally different, and the significant difference of diffraction peaks detected from the top of Sample A and B clearly shows the perfect orientation of NG. [50,51] As shown in Figure 3a,b, the XRD diffraction patterns obtained from Sample A and Sample B are totally different, and the significant difference of diffraction peaks detected from the top of Sample A and B clearly shows the perfect orientation of NG.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon-based materials and metallic fillers such as graphite [5], graphite/graphene nanoplateles (GNPs) [6,7], graphene [8], carbon nanotubes (CNTs) [9], carbon fiber [10,11], silver particles, silver nanowires [12], and copper nanowires [2,13] have been widely utilized to fabricate polymer-based TIMs owing to their extraordinary inherent thermal conductivity [14,15]. However, the incorporation of electrically conductive fillers will inevitably cause the great deterioration of electrical insulation performance, which hinders the wide use of these TIMs in next-generation microelectronics devices [16,17] such as LED devices with chips directly placing on the heat sink, single chip packages [18], and high-voltage devices.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pure graphene films with a high in-plane thermal conductivity of 1940±113 W m −1 K −1 have been fabricated [31]. [47][48][49], and constructing a segregated structure [5,[50][51][52]. Vertically aliened CNT (VACNT) composites fabricating by the CVD method can provide a high through-plane thermal conductivity and can be used as TIMs [53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation